Revisiting Microsurgical Distal Bypass for Critical Limb Ischemia - Tanaka, Yoshio; Uemura, Tetsuji; Ayabe, Shinobu; Hirao, Tomohiro; Nagasao, Tomohisa (Journal of Reconstructive Microsurgery, 2016)
Background The purpose of this study was to investigate the efficacy of introducing microsurgical techniques to distal bypass surgery for critical limb ischemia.Methods Datasets of 83 consecutive microsurgical distal bypasses in a multicenter (SKY) study were compared with the results of the PREVENT III (PIII) study regarding the following: (1) patients' characteristics, (2) clinical severity according to the PIII risk score, (3) conduits and procedures for revascularization, (4) proximal and distal anastomosis sites, and (5) primary patency and amputation-free survival (AFS) rates at 1 year.Results The high-risk group in the SKY study was larger compared with that in the PIII study (37 vs. 9%, respectively; p < 0.0001). Although all patients underwent revascularization in the perimalleolar region (100 vs. 65.1%, respectively; p < 0.0001), the primary patency rate at 1 year was 71.8%, compared with 59.9% in the PIII study (p = 0.0227). The AFS rate at 1 year was not significantly different between the SKY and PIII studies (80.6 vs. 75.1%, respectively; p = 0.189); however, there was a significant difference between the high-risk subsets of each group: 74.1% in the SKY study and 45% in the PIII study (p < 0.0001).Conclusions Our data demonstrated that microsurgical distal bypass is an effective and durable procedure, especially for high-risk patients. We believe that microsurgical techniques should be considered for distal bypass to optimize the treatment of ischemic limbs with severe peripheral artery disease.
Keywords: distal bypass; critical limb ischemia; limb salvage